Effects of famotidine use during pregnancy: an observational cohort study - Ayako Nishimura; Ayako Furugen; Masaki Kobayashi; Yoh Takekuma; Naho Yakuwa; Mikako Goto; Masahiro Hayashi; Atsuko Murashima; Mitsuru Sugawara (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Famotidine, a histamine2-receptor antagonist (H2Ras), is widely used to treat and prevent gastrointestinal symptoms during pregnancy. Although several studies have reported the use of H2Ras during pregnancy, limited data on famotidine were included in these reports. Therefore, we analyzed pregnancy outcome data to evaluate the effects of famotidine use during pregnancy on the fetus. Methods Pregnancy outcome data were used for females enrolled in two Japanese facilities that provided counseling on drug use during pregnancy between April 1988 and December 2017. For the primary endpoint, the incidence of congenital malformations was calculated from the data of live birth to pregnant women who took famotidine (n = 330) or drugs considered to exert no teratogenic risk (control, n = 1,407) during the first trimester of pregnancy. Considering secondary endpoints, the incidence of obstetric outcomes, including preterm delivery, was calculated from data on the use of famotidine (n = 347) and controls (n = 1,476) during the entire pregnancy. The crude odds ratios (cORs) for the incidence of congenital malformations were calculated using univariate logistic regression analysis, with the control group used as the reference. Adjusted ORs (aORs) were calculated using multivariate logistic regression analysis adjusted for various other factors. Results The incidences of congenital malformations in the famotidine and control groups were 3.9% and 2.8%, respectively. There was no significant difference between the famotidine and control groups (cOR: 1.40 [95% CI:0.68–2.71], aOR: 1.06 [95% CI:0.51–2.16]). Conversely, the preterm delivery rates were 8.1% and 3.8% in the famotidine and control groups, respectively, indicating a significant difference (cOR: 2.00 [95% CI:1.20–3.27]). However, the multivariate analysis eliminated famotidine use as a confounding factor. Conclusions This observational cohort study revealed that exposure to famotidine during the first trimester of pregnancy was not associated with an increased risk of congenital malformations in infants. Although a higher rate of preterm delivery was detected in famotidine users when compared with controls, this could be attributed to confounding factors, such as complications.